MENINGKATKAN LITERASI DIGITAL MELALUI PELATIHAN MICROSOFT OFFICE: STUDI KASUS SISWA/SISWI MA MAARIF NU CIMANGGU - Tasdik, Komarudin (Jurnal Pengabdian Kepada Masyarakat Babakti, 2023)
In this era of globalization, technology is an inseparable part of society, technology is also an infrastructure in learning activities. In facing the times, education and technology must go hand in hand. Therefore, Microsoft Office training is one of the software that can be used to support education. Microsoft office is a software made by Microsoft and designed to run under the operation of Microsoft Windows. Microsoft Office training provided is Excel, Word, Powerpoint. The purpose is as an activity to practice knowledge that is accepted directly or tangibly in the community. The method is used with lectures and practicums. This program is attended by grade 11 students of MA Maarif NU Cilempuyang. This program is to improve performance. We hope to help participants by providing escorts to find their identity and be able to help in the world of work.